2023
DOI: 10.3390/su15064828
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Spatial and Temporal Variability and Factors Influencing the Ecological Resilience in the Urban Agglomeration on the Northern Slope of Tianshan Mountain

Abstract: Based on land-use change data, this paper constructed an ecological resilience evaluation model from the three dimensions of resistance, adaptability, and regeneration capacity. The spatial and temporal evolution characteristics of the ecological resilience of urban agglomeration on the northern slope of Tianshan Mountain (UANST) from 1990 to 2020 were studied. The key factors affecting the spatial distribution of ecological resilience were detected. The results showed that (1) from 1990 to 2020, the mean ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The regional development of North Shanxi urgently needs to strengthen its ties with other regions and form a mutual aid link for overall development to enhance the urban ecological resilience of Shanxi Province. Tong et al (2023) suggested that both natural and human factors affected the spatial distribution of ecological resilience of the northernslope of Tianshan Mountain. Shi et al (2022) suggested that socio-economic development was the main influencing factors of urban ecological resilience.…”
Section: Discussionmentioning
confidence: 99%
“…The regional development of North Shanxi urgently needs to strengthen its ties with other regions and form a mutual aid link for overall development to enhance the urban ecological resilience of Shanxi Province. Tong et al (2023) suggested that both natural and human factors affected the spatial distribution of ecological resilience of the northernslope of Tianshan Mountain. Shi et al (2022) suggested that socio-economic development was the main influencing factors of urban ecological resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Land is the foundation for rural social and economic activities, and any alterations in land use mirror the dynamic repercussions for rural social-ecological systems (Skerratt 2013, Berke and Ross 2013, Tong et al 2023. Ecosystem services encompass the conditions of the natural environment and the benefits generated by ecosystems during the ecological processes that sustain human existence, which are often discernible through land-use changes (Yin et al 2021).…”
Section: Substitution Methodsmentioning
confidence: 99%
“…Ecosystem services encompass the conditions of the natural environment and the benefits generated by ecosystems during the ecological processes that sustain human existence, which are often discernible through land-use changes (Yin et al 2021). There is a noteworthy correlation between ecological resilience and ecosystem services (Tong et al 2023). Some scholars have calculated the value of ecosystem services in China using the value equivalent factor method per unit area, referencing the prices of China's three major grain crops (Xie et al 2015a, Xie et al 2015b).…”
Section: Substitution Methodsmentioning
confidence: 99%
“…The values of NDVI have a range of (+1 to -1) in general, if the result is positive, it is an indicator that the cell has a plant cover, and the higher the resulting positive value, the greater the vegetation, and density of the plants and have healthier and the opposite is true with regard to the negative values that indicate non-green surface features [23,24].…”
Section: Normalized Difference Vegetation Index (Ndvi) Calculationmentioning
confidence: 99%